2015
DOI: 10.4238/2015.march.6.5
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor gene CAG repeat polymorphism and risk of isolated hypospadias: results from a meta-analysis

Abstract: ABSTRACT. Studies investigating the association between the CAG repeat polymorphism and the risk of isolated hypospadias have reported conflicting results. The aim of this study was to quantitatively summarize the evidence for such a relationship. Two investigators independently searched the Medline, Embase, CNKI, and Wanfang databases. Weighted mean difference and 95% confidence intervals for the CAG repeat polymorphism and isolated hypospadias were calculated using a random-effects model. Subgroup analyses w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…The microsatellite polymorphism in the AR gene, which causes variation in glutamine amino acid residues, was examined in a metaanalysis of 444 patients with isolated hypospadias and 727 controls. It was shown that longer CAG tracts were associated with an increased risk of hypospadias [Huang et al, 2015]. A similar effect was reported by Wang et al [2018] in relation to the association between longer CAG/GGC repeats and cryptorchidism.…”
Section: Resultssupporting
confidence: 59%
“…The microsatellite polymorphism in the AR gene, which causes variation in glutamine amino acid residues, was examined in a metaanalysis of 444 patients with isolated hypospadias and 727 controls. It was shown that longer CAG tracts were associated with an increased risk of hypospadias [Huang et al, 2015]. A similar effect was reported by Wang et al [2018] in relation to the association between longer CAG/GGC repeats and cryptorchidism.…”
Section: Resultssupporting
confidence: 59%
“…Till date, both population based case-control and genome-wide association studies have shown some genes to be associated with hypospadias. Most assessed Populationbased: Case-Control Association Studies like Diacylglycerol Kinase Kappa (DGKK6)-converts diacyl glycerol to phosphatidic acid-rs4554617, Master Mind Like domain (MAMLD1) mutations/inframe splice variants generating dysfunctional proteins and/or unstable mRNAs (Liu et al 2017); Steroid 5-alpha reductase (SRD5A2-V89L) -Conversion of testosterone to dihydrotestosterone (Samtani et al 2011), Steroid 5-alpha reductase (SRD5A2-A49T, SRD5A2-R227Q) and TA repeat gene polymorphisms (Samtani et al 2015), MAMLD1-activates promoter of non-canonical NOTCH target Hes 3 promoter (Novel-P299A misense and c.2960C>T in in 3' UTR of Exon 7; (Ratan et al 2016), CYP17A1-Conversion of pregnenolone and progesterone (Samtani et al 2010;Qin et al 2012), Hydroxy Steroid 17-b dehydrogenase (HSD3B2)-Interconversion of androgens and progesterone related hormones (Codner et al 2004), Hydroxy Steroid 17-b dehydrogenase HSD17B3-Interconversion of oestrogens and androgens (Sata et al 2010), CYP1A1-Contributes to 2-alpha hydroxylation of oestrogens (Kurahashi et al 2005), Androgen receptor gene CAG repeat polymorphism and risk of isolated hypospadias (Huang et al 2015) and Tissue-specific roles of FGF signaling in external genitalia development. (Harada et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It is hypothesized that hypospadias, as a clinical presentation of the wide clinical spectrum of “testicular dysgenesis syndrome,” is a consequence of environmental interaction with polymorphic genes along the androgen‐signaling process. Prenatal diagnosis of male genital anomalies is considered a challenging sonographic issue because of a wide clinical spectrum .…”
mentioning
confidence: 99%
“…1 However, a recent review of the literature regarding the worldwide prevalence of hypospadias 2 reported geographic, regional, and ethnic differences, with an extreme heterogeneity of published studies and contradictory reports on rising hypospadias rates. [3][4][5] It is hypothesized 6 that hypospadias, as a clinical presentation of the wide clinical spectrum of "testicular dysgenesis syndrome," 7,8 is a consequence of environmental interaction 9 with polymorphic genes 10,11 along the androgen-signaling process. Prenatal diagnosis of male genital anomalies is considered a challenging sonographic issue because of a wide clinical spectrum.…”
mentioning
confidence: 99%